Педагогик тизимларда синергЕТИКА тамойиллари - Душабоев, О.Н. (SCIENCE and SOCIETY, 2020)
The article is devoted to consideration of synergetics as the new approach in modern education system. Different points of views on synergetics as methodology of modern science are considered. In frame of system, there were studied hierarchy of edicational and Pedagogical teaching aims, informational-technological provision of educational process, synergetic of education, teaching and upgrowing, which consists of components of internship and teacher. Here are given examples of seven main homeostatistical, hierarchical, non-linear, unstable, closed (open), dynamic hierarchy, observing principles of synergetic, in pedagogical systems.